Bird Use of Linear Areas of a Tropical City: Implications for Park Connector Design and Management - Sodhi, Navjot S. (Institutional Knowledge at Singapore Management University, 1999)
The National Parks Board of Singapore has plans to link up all urban parks and native habitats through a park-connector network. Although this connector network has already been implemented, it will take about 30 years to complete. We surveyed birds in 10 linear areas in Singapore. Of these linear areas, two were already completed park connectors, six were parks, and two were located in rainforest edges. We assessed and compared bird communities among these 10 sites. We also determined how the characteristics of these linear areas affect bird diversity and abundance. One of the established park connectors, the Ulu Pandan Canal, attracted 67 bird species, and its bird community was similar to a linear park (Kent Ridge Park). The other recently completed connector, the Jurong Canal, had only 37 bird species. Based on characteristics (percentage of area covered by built environment, open space, vegetation and water) within and surrounding the sites, we found that with increases in built areas, higher abundance of human-associated bird species (e.g. House Swift, Apus nipalensis and Common Myna, Acridotheres javanicus) was found at the sites. Similarly, the increase in vegetation cover (both native and managed) increased the abundance of parkland and rainforest-associated bird species (e.g. Greater Green Leafbird, Chloropsis sonnerati and Short-tailed Babbler, Malacocincla malaccensis). For completed connectors, landscape and management planners should preserve the existing diversity of habitats surrounding the connectors. Similar steps should be taken for the design of future park connectors. © 1999 Elsevier Science B.V. All rights reserved.